Efficacy and Safety of Probiotics for the Treatment of Alzheimer's Disease, Mild Cognitive Impairment, and Parkinson's Disease: A Systematic Review and Meta-Analysis - Xiang, Shuai; Ji, Jin-Long; Li, Sha; Cao, Xi-Peng; Xu, Wei; Tan, Lan; Tan, Chen-Chen (Frontiers in Aging Neuroscience, 2022)
Background: Alzheimer's disease (AD) and Parkinson's disease (PD) are two of the most common neurodegenerative diseases, and mild cognitive impairment (MCI) is considered a prodromal stage of clinical AD. Animal studies have shown that probiotics can improve cognitive function and mitigate inflammatory response, however, results from randomized controlled trials in humans are still unclear. Objectives: A systematic review and meta-analysis was conducted to evaluate the efficacy and safety of probiotic therapy on cognitive function, oxidative stress, and gastrointestinal function in patients with AD, MCI and PD. Methods: We searched the electronic databases such as PubMed, EMBASE, Cochrane Library until October 2020 for the eligible randomized controlled trials, as well as the unpublished and ongoing trials. Our primary endpoints were cognitive function, inflammatory and oxidative stress biomarkers, gastrointestinal function, and adverse events. Results: After screening 2459 titles and abstracts about AD or MCI, we selected 6 eligible studies (n = 499 patients). After screening 1923 titles and abstracts about PD, we selected 5 eligible studies (n =342 patients). Compared with the control group, treatment with probiotics improved the cognitive function of patients with AD in the intervention group (P=0.023). Cognitive function also improved in MCI patients (P=0.000). Inflammation-related indicators: Malondialdehyde (MDA) was significantly reduced (P=0.000); and hs-CRP decreased (P=0.003). Lipid-related indicators: VLDL decreased (P=0.026); triglyceride decreased (P=0.009); and insulin resistance level improved: decreased Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) (P=0.019). Conclusion: Our analyses suggest that probiotics can improve cognitive and gastrointestinal symptoms in patients with AD, MCI and PD, which is possibly through reducing inflammatory response and improving lipid metabolism. The safety has also been proven. However, more RCTs with rigorous study design are needed to support our findings.